Luisa Ricaldone, Ritratti di donne da vecchie (Guidonia, RM, Iacobelli Editore, 2017, 136 pp. ISBN 9788862523790) (Altre Modernità, 2018)
Luisa Ricaldone, Ritratti di donne da vecchie (Guidonia, RM, Iacobelli Editore, 2017, 136 pp. ISBN 9788862523790)di Michela Volante